Strategi Politik Pan-Islamisme Sultan Abdul Hamid II (1876-1909 M) - Afifah Alawiyah,; Muhammad Faiz,; Muhammad Masruri, (Advances in Humanities and Contemporary Studies, 2024)
Sultan Abdul Hamid II was appointed Caliph of the Ottoman State on August 31, 1876 AD. The period of leadership of the sultans before Abdul Hamid II came to power was more inclined towards the West, causing the Ottoman State to experience various problems, especially westernization and secularization which had an impact on political, social and religious dynamics. Sultan Abdul Hamid II brought his own approach to his leadership with the aim of restoring stability to the Ottoman State and strengthening Muslims with the political policy of Pan-Islamism. This vision of Pan-Islamism as a means to unite Muslims around the world, aligned with his broader strategy to stabilize Ottoman Dynasty during a period of significant challenge. This study uses qualitative research methods with a focus on critical analysis related to the history of the Ottoman Empire, combining library research techniques, which involves collecting references from books, journals, articles, theses, and other relevant literature related to the history of Ottoman Turkiye's Pan-Islamism policy. The results of this study conclude that the strategies carried out by Sultan Abdul Hamid II in realizing his political policy of Pan-Islamism include: a.) Mass media propaganda strategy, b.) Consular dispatches to various Muslim regions, c.) Development of a transportation system, d.) Campaign to advance education, and e.) Strategy to advance the economy.